Postoperative prolonged mechanical ventilation correlates to poor survival in patients with surgically treated spinal metastasis - Hamed, Motaz; Brandecker, Simon; Rana, Shaleen; Potthoff, Anna-Laura; Eichhorn, Lars; Bode, Christian; Schmeel, Frederic Carsten; Radbruch, Alexander; Schäfer, Niklas; Herrlinger, Ulrich; Köksal, Mümtaz; Giordano, Frank Anton; et al. (Frontiers in Oncology, 2022)
Objective Patients with spinal metastasis (SM) are at advanced stages of systemic cancer disease. Surgical therapy for SM is a common treatment modality enabling histopathological diagnosis and the prevention of severe neurological deficits. However, surgery for SM in this vulnerable patient cohort may require prolonged postoperative intensive care treatment, which could adversely affect the anticipated benefit of the surgery. We therefore assessed postoperative prolonged mechanical ventilation (PMV) as an indicator for intensive care treatment with regard to potential correlations with early postoperative mortality and overall survival (OS). Methods Between 2015 and 2019, 198 patients were surgically treated for SM at the author´s neurosurgical department. PMV was defined as postoperative mechanical ventilation of more than 24 hours. A multivariate analysis was performed to identify pre- and perioperative collectable predictors for 30 days mortality. Results 20 out of 198 patients (10%) with SM suffered from postoperative PMV. Patients with PMV exhibited a median OS rate of 1 month compared to 12 months for patients without PMV (p < 0.0001). The multivariate analysis identified “PMV > 24 hrs” (p < 0.001, OR 0.3, 95% CI 0.02-0.4) as the only significant and independent predictor for 30 days mortality (Nagelkerke’s R2 0.38). Conclusions Our data indicate postoperative PMV to significantly correlate to high early postoperative mortality rates as well as to poor OS in patients with surgically treated SM. These findings might encourage the initiation of further multicenter studies to comprehensively investigate PMV as a so far underestimated negative prognostic factor in the course of surgical treatment for SM.